Reclaiming languages and preserving identities - Oliveira, Manuela Correa (Revista da ABRALIN, 2020)
David Bradley claims there must be a mindset shift in terms of the treatment given to endangered languages. For that matter, “dead language” is no longer acceptable, but rather “sleeping language”, for instance. Providing examples of awakened languages, such as Lisu and Bisu, Bradley reaches out linguists and non linguists to reclaim languages in order to protect cultural identities. In spite of the work being done by scholars, the presenter argues that research on endangered languages must have governmental support along with universities and other authorities. It is only with conjoined forces that languages can be reclaimed and cultural identities can be preserved.